“Implementación de un modelo piloto para la gestión de la cadena de suministros utilizando BLOCKCHAIN”. - Manobanda Paucar, Christian Danilo (2021)
In the different industries, problems are generated within the management of the supply chain in which there is no transparency in the entry of product information in each process, which generates poor control in the traceability of the entire system, which generates inconsistencies in the records. The objective of this research project is to implement a pilot model for supply chain management using Blockchain technology. For this, an investigation was carried out with a descriptive approach, addressing a synthetic analytical method, for which the bibliographic method was used, in the investigation two case studies were analyzed where the generalities of each of them were analyzed, their advantages and disadvantages as well of its components. To understand how this technology works, it was necessary to investigate how transactions with cryptocurrencies (BITCOIN) are carried out and each of the steps needed to carry out a secure transfer free of document forgery was analyzed. Subsequently, a pilot model was carried out with the Blockchain technology of the case study to have a better transparency of the information records and to have a better traceability in the production processes of a food industry. It can be obtained from the developed pilot model, it complies with the three technical foundations of Blockchain technology, which is distributed registration, immutability, traceability, but it cannot compete with applications developed on specialized platforms, even so xvii The research project was successfully developed within the fundamental parameters of a Blockchain technology.